How can school – parental participation support the generation of social capital for parents? - Cleland, Jonathan; Lumsdon, David (Educational and child psychology, 2021)
Aim: This meta-ethnography views social capital as a resource to be generated, within contexts of parental participation with schools, offering possibilities for a positive change in power relations, and the addressing of social justice concerns. Rationale: Increased parental participation with children’s learning has a positive impact on children’s achievements. When participation does not happen, responsibility is often placed with ‘hard to reach’parents. Social capital theory suggests parents differ in their access to capital that affects their ability to act and participate with schools. This meta-ethnography explores examples of parent-school relations which impact positively on parents, regarding empowerment, parent voice and social capital. Findings: Key concepts generated were ‘Cultural and Social Factors’, ‘Parental Expectations’, ‘Communication’, ‘Belonging’ and ‘Influence’. A framework is presented addressing the five themes across three levels. The findings emphasised the importance of relational justice in parental participation with schools, and listening to others as an act of recognition. Limitations: Given the interpretive nature of meta-ethnographic research, there are limitations to the generalisability of the findings. However, qualitative research enables us not to predict but anticipate what might be involved in analogous situations. Conclusions: Schools should invest in understanding the cultural and social lives of their pupils’ families, as well as parents’ expectations around participation. This should lead to improved communication and relationships with parents, supporting a sense of belonging. Schools should look for opportunities to promote parental agency and competence, to work collaboratively with parents, and to empower parents in how they engage with their children’s learning.